Penilaian Tingkat Kesehatan Perbankan Melalui Camel Analysis Pada PT. BANK HSBC INDONESIA - Maulana, Wahyu (Unversitas Islam Madura, 2018)
Look at the development and increasing of the borne risks by banking especially on the credit problem; with the result that it is impacted on the level of the customer confidence, thus, banking must improve their performance. With the existence of the improvements mentioned in the internal and management, then, the performance of the banking system and customer confidence will naturally improve. Based on those conditions, the writers conducted this study to assess the performance of one of the foreign exchange National Private Banking (BUSN) in Indonesia. The population of this study is PT. Bank HSBC Indonesia which is registered with OJK (Financial Services Authority). The purpose of this study is to find out, assess, and analyze the performance of PT. Bank HSBC Indonesia using CAMEL analysis. The data used is a collection of financial statements per quarter of 2017 along with the literature reviews. For the technique of data analysis, this study used the CAMEL analysis which is assessed from the several aspects of assessment, including: Capital (CAR), Assets (KAP), Management (NPM), Earning (ROA and BOPO), and Liquidity (LDR). Based on the discussion and results of analysis in this study, the writers concluded the several points: 1. the aspects of capital and earnings are very healthy; 2. aspects of assets and management are quite healthy; and 3. the liquidity aspect is not healthy. The whole statements, the health level of PT. Bank HSBC Indonesia in 2017 which was assessed using the CAMEL analysis is unhealthy.